Mobile Inquiry and Conceptual Learning: Linguistic and Educational Perspectives in Digital Classrooms - Francesca Romano (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2009)
The integration of mobile technologies in education has transformed traditional learning environments into more interactive and student-centered spaces. Within the interdisciplinary framework of linguistics, arts, and education, mobile inquiry-based learning offers new opportunities to enhance conceptual understanding through language-mediated interaction, creative engagement, and digital exploration. This study examines how smartphone-based inquiry learning supports students’ conceptual mastery in introductory-level education, with particular attention to the role of language use, communication processes, and digital learning practices. The findings indicate that mobile inquiry-based learning significantly enhances students’ conceptual understanding while simultaneously promoting active communication, collaborative meaning-making, and creative problem-solving. From a linguistic perspective, the use of digital tools encourages dialogic interaction and supports the development of academic language. From an educational standpoint, it fosters learner autonomy and critical thinking, while also integrating elements of creativity associated with arts-based learning. This study highlights the importance of incorporating mobile technologies as part of an interdisciplinary pedagogical approach that connects language, creativity, and conceptual learning. It suggests that educational practices aligned with digital inquiry can contribute to more meaningful and engaging learning experiences in contemporary classrooms.